Hepatoprotection and hepatotoxicity of Heshouwu, a Chinese medicinal herb: Context of the paradoxical effect. (October 2017) - Li, Hongliang; Wang, Xuanbin; Liu, Ying; Pan, Dongfeng; Wang, Ye; Yang, Nian; Xiang, Longchao; Cai, Xiaojun; Feng, Yibin
Abstract: Heshouwu ( Polygonum multiflorum Thunb.) has been a common Chinese medicine and a folk Taoist medicine for over a thousand years. There are two drug forms, Shengshouwu ( Polygoni Multiflori Radix ) and Zhiheshouwu ( Polygoni Multiflori Radix Prapaerata ) in the Chinese Pharmacopoeia. In this review, we retrieved articles with such keywords as Heshouwu, liver protection and liver toxicity in the databases of PubMed and the China National Knowledge Infrastructure (CNKI). Hepatoprotection and hepatotoxicity of Shengshouwu and Zhiheshouwu in vitro and in vivo, and their clinical settings and adverse drug reactions (ADR) were summarized, analyzed and critically reviewed. In bench research, both drug forms had effects against nonalcoholic fatty liver disease, oxidation, fibrosis, cirrhosis, and liver cancer. Clinically, Heshouwu was used for treating fatty liver disease (FLD), hyperlipidemia, cirrhosis and hepatitis B. In contrast, both drug forms could lead to drug-induced liver injury and even death in vitro, in vivo and in clinical settings. In addition, the active components of both drug forms had hepatic benefits and toxicity in interaction with emodin, physcion, and probably 2, 3, 5, 4′-tetrahydroxy-stilbene-2-O-beta- d -glucoside (TSG). In conclusion, Heshouwu exhibited both hepatoprotection and hepatotoxicity. It is essential to evaluate the advantages and disadvantages when Heshouwu is in clinical use. Graphical abstract: Highlights: Heshouwu includes two preparations for medical use, Shengshouwu and Zhiheshouwu. Both Shengshouwu and Zhiheshouwu exert liver protection and toxicity. Hepatotoxicity may mainly stem from anthraquinones. The component interactions may enhance both protection and toxicity.